PENGARUH DOSIS PUPUK KANDANG SAPI DAN MIKORIZA TERHADAP PERTUMBUHAN TANAMAN JAGUNG (Zea mays L.) - Wiyono; Setie Harieni; Daryanti; Agus Budiyono; Qoirul Umam (JURNAL ILMIAH AGRINECA, 2021)
In Indonesia, maize is the second important food crop after rice. Corn is a potential raw material for the food industry, processed products for home industries, as well as feed so that the need continues to increase. Meanwhile, maize production is currently not sufficient to meet the needs, so the shortage is still met from imports. This study aims to determine the effect of cow manure and mycorrhizal doses on the growth of maize (Zea mays.L). The research was conducted in Gejugan Village, Andong District, Boyolali Regency, with a height of 154 m above sea level on the Grumusol soil type. This study used a completely randomized block design (RAKL) with two treatment factors, namely cow manure dosage factors (0, 10, 20, and 30 tonnes/ha) and mycorrhizae (0, 5, 10 g / plant) with 3 replications. The results showed that the dose of cow manure affected the growth of maize plants, while the mycorrhizal dose only affected the growth of corn plant roots. The interaction effect of cow manure dose with mycorrhizae occurred on root growth of corn plants. The best maize growth was obtained in the combination of 30 ton/ha manure dose treatment with 10g / plant mycorrhizae which produced the highest dry weight of stover (97.39 g), and the lowest dry weight (61.00 g) was obtained in the treatment without cow manure and mycorrhizae.